Single-ended traveling wave fault location on radial distribution lines - Coggins, David Paul (2010)
In this thesis a single-ended traveling wave fault location algorithm is developed for autonomously locating short circuit faults on a radial distribution line using the high frequency traveling wave transients. The traveling wave pattern observed at the sub-station is correlated with the traveling wave pattern predicted using time tree analysis for different fault locations and fault resistance. Genetic search techniques are used to evolve an initial population of possible fault locations to determine the most likely fault location. It is shown through extensive EMTP simulations that the scheme is capable of finding the location of three phase faults, inter-phase faults and single-phase faults for fault resistances ranging from 0 - 1000 ohm on a radial distribution line with five sub-feeders.